Responding to Future Regime Shifts with Agrobiodiversity: A Multi-level Perspective on Small-scale Farming in Uganda - Marta, Kozicka; Gotor, Elisabetta; Ocimati, Walter; Kikulwe, Enoch; Groot, Jeroen C.J. (Agricultural Systems, 2020)
We analyse the impact of two large-scale regime shifts caused by disease incidence or climate change, and associated crop productivity and price changes, on banana-based smallholders in Uganda. We evaluate these farmers' vulnerability and assess the potential of using increased crop diversity to improve their resilience. We further explore trade-offs and synergies between environmental, economic and nutritional outcomes faced by the farmers in their decision making when a regime shift occurs. We simulate the large-scale scenarios with the IMPACT model and use the results obtained to assess their effect at the local level using the bio-economic farm-household model, FarmDESIGN. Our results indicate that climate change can lead to a regime shift that expands revenue variance, increases soil erosion and reduces vitamin A yield for farmers. Banana disease can negatively impact income levels and species diversity. We show that under both scenarios farmers have scope to reconfigure their farms and recover farm performance. Specifically, we discuss the benefits of species diversity; increasing agrobiodiversity by adding new crops increases the farm's adaptive capacity and resilience, allowing for much higher revenues, on-farm crop diversity and vitamin A production. The conceptual approach and the method we developed can be applied to assess the local synergies and trade-offs between crop diversity conservation, nutrition, environmental protection and human nutrition that farmers face as a result of global drivers. Our results offer a further understanding of how biodiverse systems respond to regime shifts, which can inform effective policy design. Our method can be also useful to help farmers manage their farms in a way to better meet their complex needs.
Keywords: Banana disease; Agricultural biodiversity; Climate change; Vulnerability and resilience; Integrated modelling; Smallholder farmer